President Costa Gomes announces the extension of the revolutionary council. F.l.t.r.: Gonçalves, Gomes and Azevedo - Singels, Han
President Costa Gomes announces the extension of the revolutionary council. F.l.t.r.: Gonçalves, Gomes and Azevedo.